DIGITALIZATION OF THE ECONOMY AND ITS NETWORKS - Abdushukurova Sevinch Akramjonovna (Journals Park Publishing, 2024)
Nowadays, techniques and technologies are developing more and more. In this article, the digitization of the economy and its sectors and the introduction and effectiveness of new techniques and technologies.
Keywords: Economy, digital economy, digitization, digital technologies.